PHYSICAL ACTIVITY IN REHABILITATION AFTER CEREBROVASCULAR ACCIDENT (CVA) - AN EXPERIENCE IN JOINVILLE / SC (Fiep Bulletin - online, 2016)
INTRODUCTION: brain (stroke) accident, or cerebrovascular (stroke) accident is characterized by rapid loss of neurological function due to blockage (ischemia) the interruption of blood supply of the brain structures or rupture (hemorrhage). The stroke patient loses much of its capacity and aerobic exercise done correctly is essential in the rehabilitation of patients who suffered a stroke. The work presented here aims to demonstrate a methodology to monitor the work of recovery after stroke and determine possible changes in the parameters of overall quality of life, through the vitals of these individuals, after conducting a regular program of physical and recreational activity. Encouraging regular physical activity and good eating habits rescue, aimed at maintaining physical and mental health, which should be a priority in the current, otherwise society, the stroke will increasingly have space in reality the population. OBJECTIVE: This project aimed to clarify the importance of practice and physical activities such as walking, cycling, treadmill running in the street rehabilitation. METHODS: Initially, it was made an explanation about the project work and the awareness of the patient in recovery. The project also involved research and preparation of material for exhibition. The patient's recovery was assessed during the year 2013, through the month of October 2014, involving such things as age, weight and height to establish the anthropometric profile. Finally prescribed physical activities. CONCLUSION: These results show that physical activity provides improvement in the general conditions, anatomical, physiological and also self-esteem and social benefits. The successful accomplishment of this work is an incentive for program expansion and development of new projects.
Keywords: Stroke; Aerobic and quality of life.